Adjuvants and autoimmunity - Israeli, Eitan (Henry Stewart Talks, 2010)
Adverse effects of adjuvants, Development of new adjuvants, Adjuvants developed to mimic TLR ligands, Adjuvants inflict themselves through autoimmune illnesses, Silicone as an adjuvant and connective tissue disease, Gulf War Syndrome, Macrophagic myofaciitis, Future adjuvants may bypass the TLR signaling pathway in order to circumvent local inflammation and the general malaise
Reviewed at 2022/04/12